DETERMINATION OF TOTAL PHENOLIC LEVELS OF EXTRACTS AND FRACTIONS OF KEPUNDUNG LEAVES (Baccaurea racemosa) - sahila, Dinda (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2024)
Baccaurea racemosa is one of the medicinal plants whose leaves are empirically used to treat diarrhea and launch menstruation. This activity was obtained because B. racemosa leaves contain metabolite compounds such as flavonoids and phenolics. Several studies have shown that the phenolic compounds contained in B. racemosa leaf extract have potential antioxidant activity. However, research on the levels of total phenolic compounds contained in the extract and fractions of Kepundung leaves (B. racemosa) has not been sufficient. Therefore, this research was conducted to determine the levels of total phenolic compounds contained in the extracts and fractions of Kepundung leaves (B. racemosa). Withdrawal of compounds was carried out using the sonication method with 96% ethanol solvent and liquid-liquid partitioning with n-hexane, ethyl acetate, and distilled water. The extracts and fractions obtained were analyzed for their metabolite profiles by test tube and total phenolic content by UV-Vis spectrophotometry. The obtained total phenolic content was then analyzed statistically using the one-way analysis of variance (ANOVA) method and followed by the Tukey test. Test-tube results showed that extracts and fractions of Kepundung leaves contained phenolic compounds, flavonoids, steroids and saponins. The total phenolic content in the 96% ethanol extract, n-hexane fraction, ethyl acetate, and distilled water respectively were 419.153 ± 1.80; 115.589 ± 1.68; 244,359; and 334.512 ± 1.29 mg gallic acid equivalent (GAE)/gram extract and fraction. The statistical test results showed that all samples had significantly different phenolic levels.